2018
DOI: 10.1016/j.jhin.2018.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Disinfection of artificially contaminated gloved hands reduces transmission of Staphylococcus epidermidis to catheter valves

Abstract: Disinfection of gloved hands is advocated increasingly in situations where visibly unsoiled gloves are used during multiple clinical activities on the same patient. As there are no data demonstrating that such practice attributes to lower bacterial transfer during clinical care, a standardized experimental study was conducted. Gloved hands touched chicken breasts contaminated with Staphylococcus epidermidis with or without disinfection before touching sterile catheter valves. Contaminated gloves transferred 5.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…This study will review the measurement methods of the primary outcome indicators, which will have reference significance for a comprehensive evaluation of the effect of glove repeated disinfection. This will guide future researchers to choose comprehensive and rational evaluation methods, such as an irrigation test16 and stretch test17 to measure glove integrity, and surface bacterial culture method18 to measure the effect of repeated glove disinfection. This study will not include a qualitative evaluation, but it will thoroughly highlight the current research direction and areas of concern.…”
Section: Discussionmentioning
confidence: 99%
“…This study will review the measurement methods of the primary outcome indicators, which will have reference significance for a comprehensive evaluation of the effect of glove repeated disinfection. This will guide future researchers to choose comprehensive and rational evaluation methods, such as an irrigation test16 and stretch test17 to measure glove integrity, and surface bacterial culture method18 to measure the effect of repeated glove disinfection. This study will not include a qualitative evaluation, but it will thoroughly highlight the current research direction and areas of concern.…”
Section: Discussionmentioning
confidence: 99%
“…In this situation, the disinfection procedure makes it safer, ensuring that the glove is visibly clean and without perforations [ 9 , 16 , 17 ]. The disinfection of gloved hands by healthcare professionals can considerably reduce the risk of contagion, when the gloves are designated for the entire patient care process and multiple tasks are carried out on the same patient [ 9 , 18 ]. Specifically, it has been shown that the efficiency of disinfection is greater for different combinations of disinfectants/gloves than for bare hands [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Staphylococcus epidermidis -комменсал кожи человека, нередко могут встречаться в одних и тех же атипичных биотопах, где они могут выступать инфекционными агентами: в мочеполовых путях (E. coli группы A -12; S. epidermidis -11.6%), в трофических язвах (E. coli -6.4-14.3; S. epidermidis -28.2%), в ожоговых (E. coli -6.3; S. epidermidis -4.4%), хирургических ранах (E. coli группы А -20 изолятов; S. epidermidis -2.2% ), на постоянных медицинских устройствах, таких как катетеры, импланты [Moet et al, 2007;DiMuzio et al, 2014;Chakraborty et al, 2015;Hinojosa et al, 2016;Козлова и др., 2017;Assadian, Humphreys, Ousey, 2018;Méric et al, 2018;Oliveira et al, 2018;Szweda, Gorczyca, Tylingo, 2018].…”
unclassified